2018
DOI: 10.1055/s-0038-1670626
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Quality of Life in Female Patients with Obesity

Abstract: Urinary incontinence impacts quality of life negatively, and the prevalence of UI is high among obese patients. In the present study, vaginal delivery and menopause were independently associated with UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…When we look at the relation of body mass index and UI; in some studies, it was found that UI is more common in women with high body mass index [15][16][17][18]. Kocak et al, in their study conducted on 1012 women aged 18-92, stated that 31.3% of women with urinary incontinence had a body mass index above 25 and 14.5% had a body mass index below 25 [9].…”
Section: Discussionmentioning
confidence: 99%
“…When we look at the relation of body mass index and UI; in some studies, it was found that UI is more common in women with high body mass index [15][16][17][18]. Kocak et al, in their study conducted on 1012 women aged 18-92, stated that 31.3% of women with urinary incontinence had a body mass index above 25 and 14.5% had a body mass index below 25 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among other risk factors of UI are BMI, type of delivery, and menopause [3,26]. We found that 90% of the participants were overweight, 76.7% had a chronic disease, 73.4% had three or more deliveries, 87.6% had vaginal deliveries, and 85.6% in the menopause period.…”
Section: Discussionmentioning
confidence: 80%
“…All patients were subjected to Interviewed International Consultation on Incontinence Questionnaire -Urinary Incontinence Short Form (ICIQ-UI SF) [7][8] was assessed degree and type of incontinence and its impact on the quality of life (total score=21 as 0 mean no incontinence and 21 means severe incontinence. (ICIQ-UI SF) include three questions items: How often do you leak urine?…”
Section: Methodsmentioning
confidence: 99%